ANALISIS RANTAI PASOK AGROINDUSTRI TEMPE DI KELURAHANGUNUNG SULAH KECAMATAN WAY HALIM KOTA BANDAR LAMPUN - Zauvi Natasena Ajusa; Zainal Abidin; Eka Kasymir (Lampung University, 2020)
This study aims to figure out the flow patterns and stakeholders of, supply chain performance of, and marketing efficiency of tempe agroindustry. Data collection was conducted in Gunung Sulah Subdistrict, Way Halim District, Bandar Lampung City from December 2018 to January 2019. This study uses a casestudy method. Determination of agroindustry sample uses purposive sampling technique and for supply chain sample uses snowball sampling technique. The data analysis method used for flow patterns and stakeholders are the supply chain system method, for the analysis of supply chain performance is SupplyChain Operation Reference (SCOR) 9.0 and for marketing efficiency analysis is the calculation of margin value, and the value of producer's share. The results of this study showed that supply chain of tempe agroindustry consisted of soybean importer, soybean agent, yeast and plastic wholesaler, soybean, yeast and plastic retailers, sub-agent of gas, producer of firewood, tempe’s agroindustries, tempe retailers, and street vendors. There is an inefficiency in cost management of Cost of Goods Sold (COGS) metric for tempe products of tempe’s agroindustry and asset management of Cash to Cash Cycle Time (CTCCT) metric for soybean, yeast, and fuel supply of tempe’s agroindustry. The most efficient marketing of tempe’s agroindustry is direct marketing to consumers with margin value of zero and producer’s share value of 100%.Key words: margin, marketing, producer’s share, supply chain, SCOR